A renaissance of microRNAs as taxonomic and phylogenetic markers in animals - Fromm, Bastian (Zoologica scripta, 2024)
Molecular markers for tracing animal sample origins and compositions are critical for applications such as parasite detection, contamination screening, and sample authentication. Among these, microRNAs have emerged as promising candidates due to their deep conservation, near‐hierarchical evolution, and stability. I here review the suitability of microRNAs as taxonomic and also phylogenetic markers and show how careful annotation efforts and the establishment of the curated microRNA gene database MirGeneDB and tools like MirMachine have revitalized microRNA research. These advancements enable accurate phylogenetic and taxonomic studies, highlighting microRNAs' potential in resolving long‐standing questions in animal relationships and extending to applications in ancient DNA and environmental RNA analysis. Future research must focus on expanding microRNA complements across all Metazoa and further improving annotation methodologies.